Seasonal Changes of Fish Assemblages in a Subtropical Lagoon in the SE Gulf of California - F. Amezcua; F. Amezcua-Linares (The Scientific World Journal)
The composition and seasonal changes of the fish assemblage in a coastal lagoon system in southeastern Gulf of California were assessed from December 2001 to July 2005. A total of 20,877 organisms belonging to 191 species and 47 families were analyzed. We determined that almost all the species inhabiting the system were found; however some rare species were not captured in our study. The majority of the species found were demersal but in every season at least one pelagic or benthopelagic species showed high abundances. The moonfish, Selene peruviana, was the most abundant species, whilst the puffer, Sphoeroides annulatus, was the main species in terms of biomass. The species composition changed seasonally; results from the Simpson diversity index and the cumulative species curve show that seasonally almost all the species in the system for a given season were found. These changes were also reflected in the multivariate results. The seasonal variations could be attributed to the migration of species out of the system as they grow and the arrival of new ones, which could also be related to temperature patterns since this environmental factor changes considerably through the year.